The impact of the organizational climate of Dhahran National Schools on professional development (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to identify the impact of the organizational climate of Dhahran Ahliyya Schools on the professional development of teachers, by answering the sub-questions. The study aimed to reveal the reality of the organizational climate in its dimensions (communications, decisions, incentives, technology, and employee care), determine the reality of practicing professional development in its dimensions (planning, training, administrative communication, resources and modern technologies), measure the degree of influence of the organizational climate on professional development, know the correlation between them, and reveal statistically significant differences according to the variables of gender and academic qualification. To achieve the study objectives, the quantitative approach was used in two ways (survey and correlation), and the questionnaire was used as a study tool. The study population consisted of all male and female teachers in Dhahran Ahliyya Schools, numbering (269) male and female teachers. A random sample of (159) male and female teachers was selected from them. The results showed that the reality of the organizational climate was high, and it was at the top of the “employee care” dimension, followed by “communications”. The reality of practicing professional development was also high, especially in the “resources and modern technologies” and “training” dimensions. The results of the linear regression revealed a statistically significant effect of all organizational climate dimensions on the dimensions of professional development, with the highest impact being "concern for employees" and "technology." The results also revealed a strong and statistically significant correlation between the dimensions of organizational climate and professional development. The results also revealed statistically significant differences in the dimensions of "decisions" and "incentives" based on gender, in favor of females. No significant differences were found based on academic qualifications. The study recommends the development of incentives that encourage creativity, the implementation of training programs to develop teachers' skills, and addressing their needs to increase their job satisfaction. It also calls for updating administrative procedures within schools to provide a stimulating work environment and enhancing the technological infrastructure through periodic updating of devices and the use of digital resources. It emphasizes the importance of designing a periodic evaluation mechanism to measure the effectiveness of organizational performance by collecting and analyzing teachers' opinions to develop programs and administrative decisions with flexibility and effectiveness.
Keywords: Organizational Climate; Professional Development; Dhahran Ahliyya Schools